Formação online de professores dos anos iniciais do ensino fundamental para o ensino de estatística: uma investigação no período remoto emergencial - Oliveira, Rayssa Melo de (2023)
Teacher professional development is a widely discussed subject and is the theme of several investigations. Despite this, it is considered that this is a non-exhausted issue. Amid the COVID-19 pandemic, which has affected school organizations around the world, investigating and reflecting on teacher's professional development, teacher's preparation policies and formative processes has become fundamental. This research addresses an investigation into a teacher formative process, in an online format, for teaching Statistics at Elementary School, during the pandemic period. The object of study was the #COmVIDa Mathematics course, from which we sought to identify contributions to the statistical formative processes of Elementary School teachers. Taking into account the participation in the online process and the discussions held in this section, the objective was to answer the following research problem: What are the contributions of an online formative process to the preparation of Elementary School teachers with regard to teaching Statistics during the period of Emergency Remote Education? To this end, the following general goal was: analyze the contributions of an online formative process for Elementary School teachers with regard to teaching Statistics, during the experience of Emergency Remote Education (ERE). The following were defined as specific objectives: Evaluate the online teacher formative process for teaching Statistics; and identify the contributions of the online formative process to teacher preparation regarding the teaching of Statistics. This was a qualitative research, based on the phenomenological-hermeneutic paradigm. The locus was the Mathematics #COmVIDa course, and the research subjects were Elementary School teachers who participated in that course. The data collection instruments consisted of the project that outlined the Mathematics #COmVIDa formative process, course syllabus, materials used by instructors in the online meetings, recordings, transcripts of meetings and the course evaluation instrument, carried out by teachers. From this analysis, the scope of #COMVIDa Mathematics course, regarding the knowledge involved in the teaching of Statistics is identified, considering that, in teachers' responses to the evaluation instrument, there was mention of aspects related to the Common Knowledge of Statistical Content, Didactic Knowledge of Statistical Content and Knowledge regarding educational objectives, goals and values. Furthermore, the relationships established between instructors and teachers contributed to the participation and involvement of course participants, in a period of environmental instability, which had a direct impact on teachers professional activities.